Comparison Of Achievement Sport Systems Between Indonesia And China - Muhammad Reza Aziz Prasetya (Journal of Physical Activity (JPA), 2022)
Sport as a model of human creation is a form of physical activity that has very complex dimensions. National development through the development of sports in Indonesia in the reform era has become a strategic vehicle, especially improving the quality of human resources, as well as the formation of national character and character, in this paper many factors play a role in success in the field of sports, one of which is here the author wants to examine the differences and similarities of the system. sports achievements between those running in Indonesia and China. This study aims to compare the development of achievement sports systems carried out in Indonesia and China in order to improve the quality and competence of sports. This study uses a qualitative descriptive method with data collection techniques through documentation studies. The results of this study conclude that the government's contribution is needed in preparing winning strategies, training facilities, increasing competition opportunities and increasing resources that can be assisted by a team of academics and researchers from universities to find new techniques in training to support the maximum use of sport science.